The Great Recession and the Future of Cities - Dethier, Jean-Jacques; Morrill, Curtis (World Bank, Washington, DC, 2014)
This paper describes the serious fiscal crisis faced by cities around the world following the Great Recession of 2008. Five years later, the after-effects of this major crisis continue to be felt and limit economic opportunities in cities. Section 1 summarizes how the crisis was triggered and how it unfolded in the US, then spread to the rest of world -- highlighting the links between financial sector and housing sector. Section 2 discusses the impact of the crisis on urban revenue and expenditure, and the stimulus programs and recovery plans devised as a short term response by cities around the world. Section 3 then discusses longer term strategies to ensure the financial, social and environmental sustainability of cities. The authors make the point -- and back up our assertions with specific examples -- that urban decision-makers must take a long view and find ways to create opportunities for their citizens, making sure that their decisions are financially sustainable in the long term. Today's decisions should not lock cities out of options tomorrow, and cities must be managed with flexibility so as to adapt to unforeseen new circumstances. The authors also argue that, while there has been a lot of talk about "smart cities" and new technologies among urban specialists and urban planners, it is ultimately the focus on basic economics (sustainable financing, providing good services to consumers and incentives for providers), good governance and good institutions that will create sustainable, dynamic and livable cities.